PENERAPAN PEMBELIAN TERSELUBUNG DALAM PENYELIDIKAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA OLEH KEPOLISIAN RESOR SIAK - ADE MARIA ENGELINA; Dessy Artina; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Undercover Buy is one of the authorities granted by the Narcotics Act to investigators of narcotics crime. The purpose of this thesis, namely; first, the application of covert purchases in the investigation of criminal acts of narcotics abuse by the Siak Resort police, secondly, obstacles in the application of covert purchases in criminal investigations into narcotics abuse by the Siak Resort police; narcotics abuse by the police of Siak Resort. The type of research used in this study is sociological legal research. Sociological legal research is carried out by making legal identification and how the effectiveness of the law applies in society. While the nature of this research is descriptive which aims to provide a detailed and clear description of the implementation of narcotics investigations using covert purchasing techniques. From the results of the research and discussion it can be concluded that first: The application of covert purchases in the investigation of criminal acts of narcotics abuse by the Siak Resort Police, is not carried out in an open manner so it is prone to mistakes made by officers, such as officers not reporting the results of investigations due to circumstances that are not possible; second, the obstacles encountered in the application of covert purchases, namely the lack of members of investigators, facilities and infrastructure, lack of budgets, field situations and people who are afraid to share information; namely proposing additional personnel to the leadership, proposing additional funds for the next year, applying for operational procurement, and using other parties to be able to deal with target. The author's advice, first: the application of covert purchasing techniques in investigating narcotics abuse must be more specifically supervised; second, the police must also provide protection for the people who have provided information on criminal acts of narcotics abuse; third, the government also pays more attention to facilities and infrastructure for the duties and functions of the police, especially in conducting investigations into criminal acts of narcotics abuse by the police of Siak Resort.